New generation post emergence herbicides for controlling weeds in Indian mustard and its efficacy on weeds in south eastern Rajasthan - B.S. Meena,; Gajendra Nagar,; Roshan Kumawat, (Annals of Agricultural Research, 2024)
Weed management in standing crop is one of the main challenges at farmer’s field. Although some of selec tive herbicides can reduce mixed weed populations, effects of these may be observable in the long-term planning. The field investigations were carried out at Agricultural Research Station, Ummedganj, Kota dur ing rabi seasons of 2018-19, 2019-20 and 2020-21 to assess evaluation of new generation post emergence herbicides for controlling weeds and its effect on yield and economics of Indian mustard (Brassica juncea L.). The field experiment comprised twelve treatments consisting of Fomesafen11.1+Fluazifop-p-butyl 11.1% SL @0.10 kg a.i./ha at 30 DAS, Fluzifop-p-butyl 13.4% EC @ 0.08 kg a.i./ha at 30 DAS, Clodinafop-propargyl 15%WP @ 0.06 kg a.i/ha at 30 DAS, Pendimethalin 30% EC @ 1.0 kg a.i. /ha PE, Quizalofop-ethyl 5% EC @ 0.035 kg a.i./ha at 30 DAS, Propaquizafop 10% EC @ 0.10 kg a.i./ha at 30 DAS, Propaquizafop 5% + Oxyfluorfen 12% EC @ 0.08 kg a.i./ha at 30 DAS (RM), Oxadiargyl 6% EC @ 0.09 kg a.i./ha PE, Oxyflurofen 23.5% EC @ 0.015 kg a.i./ha at 30 DAS, Pendimethalin 1.0 kg a.i./ha fb clodinofop- propargyl @ 0.06 kg a.i./ha at 30 DAS, Hand Weeding at 40 DAS and Weedy checkwere evaluated in randomized block design with three replica tions. Result revealed that application of pendimethalin 1.0 kg a.i./ha fb clodinofop-propargyl @ 0.06 kg a.i./ ha at 30 DAS was found more effective in reducing weed dry weight, WI and higher WCE, seed yield, stover yield, number of siliquae /plant, number of primary and secondary branches/plant closely followed byclodinafop-propargyl 0.06 kg a.i/ha at 30 DAS, propaquizafop10% EC @ 0.10 kg a.i./ha at 30 DAS, pendimethalin 30% EC @1.0 kg a.i./ha PE, quizalofop-ethyl5% EC 0.035 kg a.i./ha at 30 DAS. Hence forth, application of clodinafop-propargyl as post-emergence can be best alternate option for controlling weeds in standing crop followed by quizalofop-ethyl at 30 DAS and propaquizafop at 30 DAS. Moreover, the highest seed yield was recorded in hand weeding at 40 DAS treatment.